Long-run Models of Oil Stock Prices - Alessandro Lanza; Matteo Manera; Margherita Grasso; Massimo Giovannini (Fondazione Eni Enrico Mattei (FEEM), 2003)
The identification of the forces that drive oil stock prices is extremely important given the size of the Oil&Gas industry and its links with the energy sector and the environment. In the next decade oil companies will have to deal with international policies to contrast climate change. This issue is likely to affect companies' shareholder values. In this paper we focus on the long-run financial determinants of the stock prices of six major oil companies (Bp, Chevron-Texaco, Eni, Exxon-Mobil, Royal Dutch Shell, Total-Fina-Elf) using multivariate cointegration techniques and vector error correction models. Weekly oil stock prices are analyzed together with the relevant stock market indexes, exchange rates, spot and future oil prices over the period January 1998- April 2003. The empirical results confirm the statistical significance of the major financial variables in explaining the long-run dynamics of oil companies' stock values.
Keywords: C32; L71; Q30; Q40; 330; Cointegration; Vector error correction models; Oil companies; Oil stock prices; Hydrocarbon fuels; Energy; Non-renewable resources; Environment; Mineralölwirtschaft; Börsenkurs; Kointegration; Industrieländer; Kointegration